Screening for new causative genes and their expression profiles in patients with left ventricular noncompaction - LI Hongyan; GUO Yun; LIU Aoyi; LYU Tiewei (Di-san junyi daxue xuebao, 2022)
Objective To screen the pathogenic genes in the patients with left ventricular noncompaction (LVNC) and validate their functions in order to provide references for pathogenesis, genetic counseling and early intervention of the disease. Methods Blood samples from 3 LVNC families attending the outpatient clinic of our hospital from January 2018 to December 2020 were collected for whole-exome sequencing (WES) to obtain the possible pathogenic genes screened in all 3 families. Induced pluripotent stem cells-cardiomyocytes (IPSCs-CMs) were derived and constructed separately from LVNC patients and normal individuals. The cells were collected at different time points and validated by quantitative real-time PCR (qPCR) to observe the expression profiles of above obtained genes during induction and differentiation. Results WES screened 14 possible pathogenic genes commonly expressed in the 3 LVNC families. qPCR results suggested that the expression of these genes changed dynamically at different time points (0, 10, 20 and 30 d), and their expression differed significantly from the normal and LVNC patient groups. Conclusion There were 14 common possible pathogenic genes screened by WES in the 3 LVNC families, and they are involved in affecting cytoskeleton, cell polarity, calcium and potassium ion regulation and energy metabolism.